A DWT-SVD Hybrid Approach for Robust Digital Image Watermarking (International Journal of Engineering and Computer Science, 2018)
Digital media can be copied and modified easily nowadays leading to security issues. There is a need for protection of digital media against unauthorized access. Digital Watermarking is a technique for protecting the copyrights and unauthorized manipulation of the digital content. In this some ownership data is embedded into the digital media that can be extracted later to prove the ownership. This paper focuses on DWT - SVD hybrid approach for improving the robustness of the watermark against various attacks